A STUDY OF IMPACT OF G20 PRESIDENCY BY INDIA: SWOC ANALYIS (International Journal of Food and Nutritional Sciences, 2022)
India hosted the presidency of the G20 grouping from Indonesia on December 1, 2022. During its presidency, in a variety of social and economic sectors, India aimed to identify, highlight, build and deepen international support for vitally important issues. This G20 conference held in India is intended to continue pressing for reformed multilateralism that creates a multipolar international structure that is more accountable, inclusive, equitable and representative. India also intends to highlight inclusive growth and development at the G20 summit, placing a focus on women's empowerment and representation in essence of its G20 discussions. The G20 is an international forum for governance of the global economy, representing 85% of two-thirds of the world's population, 75% of global trade, and the worldwide GDP. India's Presidency came at a time of global flux, with the Russia-Ukraine conflict and sanctions affecting the most vulnerable developing countries and LDCs. India's vision for global development, is shaped by green and digital uprisings and the pandemic effect. With a new emphasis on the "global common good", PM Modi has changed India's foreign policy. Through its leadership of the G20, India seeks to find long-term & appropriate approaches to global problems including climate change, emerging technologies, food and energy security. The objectives of this article are to analyze the country's strengths, weaknesses, opportunities and challenges (SWOC) in the context of India in the G20 summit. The current study is conducted using secondary data from books, government publications, open-source databases, and other literature sources. It is based on both descriptive and analytical research methodologies.